1999
DOI: 10.4049/jimmunol.163.2.743
|View full text |Cite
|
Sign up to set email alerts
|

I-Ag7-Mediated Antigen Presentation by B Lymphocytes Is Critical in Overcoming a Checkpoint in T Cell Tolerance to Islet β Cells of Nonobese Diabetic Mice

Abstract: B cell-deficient nonobese diabetic (NOD) mice are protected from the development of spontaneous autoimmune diabetes, suggesting a requisite role for Ag presentation by B lymphocytes for the activation of a diabetogenic T cell repertoire. This study specifically examines the importance of B cell-mediated MHC class II Ag presentation as a regulator of peripheral T cell tolerance to islet β cells. We describe the construction of NOD mice with an I-Ag7 deficiency confined to the B cell compartment. Analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(8 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…These data also show that accelerated T1D development can occur even when limited anti-insulin IgG is present, due to IgM isotype restriction by this non-site-directed/class-switch-incompetent V H 125Tg ( 7 , 14 , 15 ). The finding that anti-insulin B cells can present autoantigen to T cells in vitro and support an Ab-independent role in driving T1D development ( 7 ) is consistent with studies showing that B cell–specific deletion of the diabetogenic MHC class II molecule, IA g7 , is also disease protective in NOD mice ( 8 ).…”
Section: Introductionsupporting
confidence: 84%
“…These data also show that accelerated T1D development can occur even when limited anti-insulin IgG is present, due to IgM isotype restriction by this non-site-directed/class-switch-incompetent V H 125Tg ( 7 , 14 , 15 ). The finding that anti-insulin B cells can present autoantigen to T cells in vitro and support an Ab-independent role in driving T1D development ( 7 ) is consistent with studies showing that B cell–specific deletion of the diabetogenic MHC class II molecule, IA g7 , is also disease protective in NOD mice ( 8 ).…”
Section: Introductionsupporting
confidence: 84%
“…T1D susceptibility and GAD-specific T cell responses were restored in NOD.Igμ mice reconstituted with syngeneic bone marrow and NOD B lymphocytes but not those with syngeneic bone marrow only [ 7 ]. NOD mice with B cell-specific deficiency in MHC class II molecule I-Ag7 are protected from T1D [ 33 ]. B-cell-depleted CD4+ NOD T cells were unable to divide in response to soluble anti-CD3 and anti-CD28 stimulation, in contrast to B6 CD4+ T cells, which underwent successive rounds of division during the culture period.…”
Section: Murine B Lymphocytes Present Islet Autoantigens To T Cells I...mentioning
confidence: 99%
“…Prior tolerization studies with BCR–CD22 colocalization focused on disease models in which antibodies are key effectors of disease including rheumatoid arthritis and alloantibody-mediated hemophilia, and these studies primarily reported in vivo antibody titer data. In type 1 diabetes (T1D), however, autoantibodies do not have such a clear role in disease, although their presence indicates risk of disease development. Rather, effector anti-islet antigen B cells are pathogenic and propagate autoimmunity via autoantigen presentation and inflammatory cytokine excretion. In addition, these prior B cell tolerization studies have primarily relied on liposome and large polymer scaffolds bearing hundreds of copies of antigen and CD22 ligand (CD22L), and less is known about the potential of low valency antigen–CD22L conjugates to tolerize B cells in a similar manner. , …”
Section: Introductionmentioning
confidence: 99%